Managing market segments with environmental concerns: geotourism and geodiversity - Sousa, Bruno Barbosa (2020)
Tourism is a multifaceted and geographically complex activity, with tourism increasingly creating new (and different) market segments with different individual interests. These segments are characterized by the motivations that make them travel and, in turn, by the differentiation of the existing offer. On the other hand, and in a recent tourist segment, geotourism, geotourists seek to enjoy contact with nature, perform sports activities and acquire authentic experiences. The present study aims to explore how this niche has developed, so it will be presented a contextualization of the concepts that are related to geotourism. Therefore, initially an approach to geodiversity and Geoconservation will be made (essential elements of this type of tourism) that will help to better understand the concept of geotourism, followed by a trip to the geosites that will end in the geoparks. Like companies, tourist destinations can also develop their own brands, becoming increasingly different and competitive destinations. Thus, this study aims to better understand the role of marketing applied to places and territories as a contribution to the tourist segmentation. In particular, a conceptual model is proposed to be tested empirically in geotourism contexts. In the end, some limitations and lines of investigation for the future will be presented. In an interdisciplinary perspective, this study presents inputs from the perspective of tourism and marketing (segmentation and consumer behavior of geotourism).